DESIGN OF A WEB-BASED TRAINING REGISTRATION SYSTEM USING RAD AT PPKD CENTRAL JAKARTA - Putra Wijaya; Syarif Hidayatulloh (LPPM Universitas Nusa Mandiri, 2026)
The annual growth of the Indonesian labor force faces challenges in employment absorption due to a competency mismatch. To address this, the government, through Bappenas, encourages vocational training programs, such as those at PPKD Central Jakarta. However, the current semi-manual registration process leads to data inefficiency and information delays. This study aims to design a web-based training registration information system using the Rapid Application Development (RAD) method. The resulting system can handle up to 17 concurrent users with an average response time of 1.25 seconds and a page load time of 4.57 seconds. PPKD Central Jakarta contributed as the research locus, providing operational data and functional requirements for system development. The implementation of this system successfully digitalizes vocational training administrative services, making them more responsive and accurate.